A bibliometric review of International Marketing Review (IMR): past, present, and future. Issue 5 (6th April 2021) - Donthu, Naveen; Kumar, Satish; Pattnaik, Debidutta; Pandey, Neeraj
Abstract : Purpose: The primary objective of this endeavour is to form a retrospective overview of the International Marketing Review (IMR ) and map its way forward. Design/methodology/approach: A range of bibliometric techniques has been employed to analyse the performance of IMR and its stakeholders, map the evolution of its thematic and intellectual structures and analyse the factors driving IMR 's academic influence and impact Findings: IMR 's academic contributions, influence and impact have grown progressively. The thematic structure of the journal has evolved into six clusters. Simultaneously, its research fronts have submerged to six bibliographic clusters, noted as marketing channels, cross-cultural impact on emerging markets, export performance, country of origin (COO), online consumers and global business environment. Among these, the first four are still evolving, suggesting scope for future submissions. Research limitations/implications: The limitation of this endeavour largely arises from its selection of bibliographic data being confined to Scopus. Originality/value: To the best of the authors' knowledge, this is the first objective assessment of the journal, useful to its authors, readers, reviewers and editorial board.